The epigram in the English Renaissance. - Hudson, Hoyt H. (Hoyt Hopewell), 1893-1944 (Princeton legacy library., 1947)
Favorite Renaissance condiment at "the great feast of language," the epigram is here presented full-flavored and various in a brilliant study by the late Hoyt Hopewell Hudson. He considers its origins, its nature, how skillfully it was shaped to eulogy and satire alike by the lively minds of its great exponents, Sir Thomas More and his contemporaries, and made the source for rigorous mental exercise in the schools. Originally published in 1947.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.